A Review of Thin-Film Growth, Properties, Applications, and Future Prospects - Sakthinathan, Subramanian; Meenakshi, Ganesh Abinaya; Vinothini, Sivaramakrishnan; Yu, Chung Lun; Chen, Ching Lung; Chiu, Te Wei; Vittayakorn, Naratip (My University, 2025)
This review article’s primary aim is to discuss different thin-film deposition technique methods and their important uses. The histories of thin-film technology, thin-film growth, thin-film classification, and thin-film preparation techniques are also covered in this review article. The preparation and characterization of functional thin films and nanostructured materials, as well as various devices based on these materials and recent developments are also focused on in this review. The properties of the materials and several thin-film deposition techniques are also covered in this article. This review article also discusses the classification and application of thin-film sensors. Furthermore, the formation of thin films and their physical properties are impacted by deposition conditions such as pH, temperature, deposition time, and deposition parameters, which are analyzed. This article discusses how a wide range of potential uses in structural, mechanical, and protective coatings; sensing; energy storage systems; catalysis; optoelectronics; and biomedicine are made possible by the special qualities of thin films and nanostructured materials, including their high surface area to volume ratio, structure, surface charge, anisotropic nature, and tunable functionalities.
Keywords: classification; deposition technique; parameters; thin-film sensors; thin-film technology